Comparison of Metabolic Syndrome, Autoimmune and Viral Distinctive Inflammatory Related Conditions as Affected by Body Mass Index - Chero-Sandoval, Lourdes; Martínez-Urbistondo, María; Cuevas-Sierra, Amanda; Higuera-Gómez, Andrea; Martin-Domenech, Eva; Castejón, Raquel; Mellor-Pita, Susana; Moreno-Torres, Víctor; Ramos-López, Omar; de Luis, Daniel; Vargas, Juan Antonio; Martínez, J. Alfredo (Journal of Clinical Medicine, 2025)
Background: Metabolic inflammation (MI), long COVID (LC) and systemic lupus erythematosus (SLE) share some metabolic common manifestations and inflammatory pathophysiological similarities. Health-related quality of life (HRQoL) and metabolic age are indicators of health status. The “METAINFLAMMATION-CM Y2020/BIO-6600” project, a prospective controlled study, aimed to identify differential diagnostic tools and clinical features among three inflammatory conditions by comparing obesity status (low BMI vs. high BMI). Methods: A total of 272 adults of both Caucasian and Hispanic descent, diagnosed with MI, LC or SLE, and a range of BMI, were recruited. Clinical and phenotypic traits were measured to analyze body composition, metabolic and inflammatory markers, HRQoL data, metabolic age and lifestyle habits using a 3 × 2 (disease × BMI) factorial design. Results: Some inflammatory related variables, such as fibrinogen, RDW (red cell blood distribution width), ESR (erythrocyte sedimentation rate) and NLR (neutrophil/lymphocyte ratio), showed effect modifications depending on the BMI and disease type. In relation to HRQoL, the Physical Component Summary (PCS12) showed no relevant changes, while the Mental Component Summary (MCS12) showed a significant effect modification according to the disease type and BMI (p < 0.05). Furthermore, a significant interaction was identified between the disease type and BMI in relation to metabolic age (p = 0.02). Conclusions: Assessing the impact of BMI on these three inflammatory diseases may help to prevent clinical complications and to design personalized treatments, especially for patients with SLE, who have a worse prognosis with an increased BMI compared to the other two inflammatory diseases.
Keywords: health markers; inflammation; long COVID; obesity; systemic lupus erythematosus